A Comparative Study Of Amlapittavinashak Yoga Kwath & Bhunimbadi Kwath In The Management Of Amlapitta W.S.R. To Acid Peptic Diseases. - Mohan, G Vinay; Mahendra, Pawar Pranita (International Research Journal of Ayurveda & Yoga, 2020)
Now a day, there are so many changes in life style, behavior and diet. To achieve our desires in limited time produces different types problems like anxiety, worry, anger, depression. In modern medical science symptomatology of Amlapittais equivalent to the features of hyperacidity. Hyperacidity and its complications pose a major threat to future public health resources throughout the world. The Ayurvedic management of Amlapitta aims not only control acid secretions in body but also to treat the root cause of the disease. People don’t follow rules like Dincharya and Rutucharya.Peoples are not awair of Rules of consumption of food which are described in “Aharvidhivishayatan” by Acharya Charak. Because of this all factor causes physiological disorders, which causes Annavaha stratus drusti which cause Mandagni and if the hetu sevan is goes on then it cause Ajeerna which ultimately leads to Aamvish .When Aamvish mixed with pittadi dosha, the original KattuRasa of Pitta changes to amla causes amalapitta disease. Amalapitta is characterised by features like Avipaak (indigestion), Klama (tridness), Utklesha (nausea), Tiktta Amlaa Udagar (sour and bitter belching), gauravata (Heaviness) ,Hrudhkantha daha (Heart and throat burning),and Aruchi. These clinical features are closely related to functional dyspepsia. All these symptoms if left untreated may produces Gastrointestinal disorder like peptic ulcer disease .Many disease like Grahani,skin disease like Shitpitta,Udard occurs as complication of Amlapitta. While describing the progonosis of Amlapitta , it has been stated that it can cured easily if promptly treated as earliest with proper Pathyapathya. The etiological factors like Abhojana, Atibhojana, ganigraha, PanchakarmaVyapat and seasonal variation etc. cause vitiation of Doshas and Agni which ultimately results Mandagni which is treated as mother of all the diseases. This Mandagni leads to Avipaka and due to Avipaka even light and small meals are not digested. This undigested and ill digested food gets shuktatva which leads to the formation of Annavisha. This Annavisha is manifestated in the form of Ajirna . As per Charaka it is said that when diet is not properly digested it gets formented and forms Annavisha. This Ama when mixed with Pitta then it develops the disease Amlapitta.